INKUBASI DESA WISATA MELALUI ICON PRODUK DAN DIGITAL MARKETING PADA DESTINASI WISATA DOMBA DESA RANCABANGO KECAMATAN TAROGONG KALER KABUPATEN GARUT - Hedi Cupiadi; Hani Siti Hanifah; Marissa Disthy Putri; Husni Muharam (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of tourism villages in Garut still faces several challenges, including the low competence of BUMDes human resources, suboptimal management transparency, and limited understanding of innovation-based tourism village concepts. In addition, inadequate infrastructure and internet access hinder digital promotion, while existing tourism products lack a strong distinctive icon as a main attraction. Business incubation programs and digital marketing initiatives have also not been optimally implemented. This Community Service Program (PKM) aims to enhance the competitiveness of Desa Wisata Domba through three main strategies: developing a distinctive product icon as the village identity, providing digital marketing training for tourism managers and MSMEs, and strengthening a business incubation program based on institutional capacity and product innovation. The activities are carried out through preparation, socialization, training, mentoring, evaluation, and dissemination stages. The expected outputs include optimization of the village’s product icon, improved human resource and institutional capacity, implementation of digital marketing practices, and the establishment of a sustainable tourism village incubation plan. The program also supports the MBKM policy by actively involving students. Through multi-stakeholder collaboration, this initiative is expected to promote more professional, competitive, and sustainable tourism village management.